Anaerobic degradation of crude oil by sulphate reducing bacteria isolated from soils contaminated with petroleum hydrocarbons - Ahmad Abd Burghal Al- Asadi (University of Thi-Qar Journal of Science, 2019)
This study included isolatation a mix cultures of sulphate reducingbacteria from soils in Shaeba regain contaminated with petroleum hydrocarbons by using APImedium enriched with oxygen reducing agents and saturated with gas (90% N2 ) and( 10% CO2 ) by using sodium lactate as solecarbon source. The result showed that the number of bacteria ranged( 4 x 105 – 4.5 x 105 ) cells / g of soil. Also using crude oil as a sole ofcarbon source to study the ability of sulphate reducing bacteria ondegradation of crude oil under anaerobic condition . The result showedthese bacteria have high ability for degradation of crude oil. The percentrate of degradation in culture was ( 84.4 % ) after (54) days incubationand the rate concentration of total petroleum hydrocarbons ( TPH )extraction from culture value ( 22.06 ) μg / L , while in control was( 190.84 ) μg / L.